2004
DOI: 10.5424/sjar/2004021-64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype x environment interactions in popcorn maize yield and grain quality

Abstract: The cultivation of popcorn in Argentina has increased greatly in the last ten years: demand by the MERCOSUR countries is high, as is profitability. Nearly all Argentine production is exported since internal consumption is tiny -less than 5% of total production. «Popped corn» is produced by the explosion of the caryopsis due to the cooking temperature. Maize kernels, which are small and hard, are composed of three structural units: the pericarp, the endosperm, and the AbstractFourteen commercial popcorn maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
7
0
3
Order By: Relevance
“…A genetic correlation not significantly different from zero would indicate that selecting families based on popping expansion would not have a significant effect on grain yield. This result is widely reported in the literature, for example, Arnhold et al (2009) and Broccoli and Burak (2004) confirmed that grain yield is inversely correlated (negative genetic association) with popping expansion. The Spearman correlation coefficient estimated by Munhoz et al (2009) was not significant for 96 S3 popcorn families.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A genetic correlation not significantly different from zero would indicate that selecting families based on popping expansion would not have a significant effect on grain yield. This result is widely reported in the literature, for example, Arnhold et al (2009) and Broccoli and Burak (2004) confirmed that grain yield is inversely correlated (negative genetic association) with popping expansion. The Spearman correlation coefficient estimated by Munhoz et al (2009) was not significant for 96 S3 popcorn families.…”
Section: Resultssupporting
confidence: 90%
“…The Spearman correlation coefficient estimated by Munhoz et al (2009) was not significant for 96 S3 popcorn families. Broccoli and Burak (2004) mentioned that the negative association between popping expansion and yield can affect the yield gains in simultaneous selection of a breeding population. From the genetic point of view, this phenomenon indicates that the two traits could be controlled by distinct genes.…”
Section: Resultsmentioning
confidence: 98%
“…[25] reported a positive correlation between ear length and grain yield. Similarly, [8] also observed positive and highly significant correlation between ear length and grain yield. [21] reported negative correlation among ear length, kernel weight and kernel rows.…”
Section: Ear Length (Cm)mentioning
confidence: 82%
“…Ziegler (2001) noted that such modifications may have to do with timely planting due to the slow germination of popcorn and harvest maturity to enable optimum popping ability. Broccoli and Burak (2004) reported high significant differences (ρ ≤ 0.01) for all characters evaluated except kernel density before expansion among fourteen (14) popcorn hybrids evaluated in two years across three environments. Genotype x Environment (G x E) interaction was also observed to be significant for the two main traits (yield and expansion volume) while the relationship between grain yield and expansion volume was negative.…”
Section: Introductionmentioning
confidence: 97%